Styrene-butadiene latex for asphalt emulsion application

By blending the styrene-butadiene copolymer at high temperature with the polymerized copolymer at low temperature, the problems of charge reversal and aggregate loss in existing asphalt compositions are solved, achieving a more economical, compatible and efficient asphalt composition.

CN119403849APending Publication Date: 2025-02-07BASF SE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380048664.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-22
Filing Date
2023-06-06
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing styrene-butadiene latex particles polymerized at high temperatures are prone to charge reversal problems, resulting in incompatible with cationic surfactants, and high aggregate loss, adhesion, solidification time and processability. Not good.

Method used

Using styrene-butadiene latex that does not require charge inversion, the polymerized styrene-butadiene copolymer at high temperatures is blended with the polymerized styrene-butadiene copolymer at low temperatures to form an economical and compatible Asphalt composition.

Benefits of technology

Improves the economy and compatibility of the bituminous composition, reduces aggregate loss, enhances adhesion and solidification time, improves processability, and eliminates the need for the use of cationic inversion surfactants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005199864190000163
    Figure BDA0005199864190000163
  • Figure BDA0005199864190000169
    Figure BDA0005199864190000169
  • Figure BDA0005199864190000281
    Figure BDA0005199864190000281
Patent Text Reader

Abstract

Disclosed herein are compositions comprising an asphalt emulsion composition having a styrene-butadiene latex. The present disclosure also relates to methods of making the disclosed compositions. The compositions disclosed herein are useful in a variety of applications, including, but not limited to, asphalt compositions, paints, coatings, carpet compositions, paper stickers or coating compositions, adhesive layers, foams, or adhesives.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates generally to asphalt emulsion compositions, and more particularly to asphalt compositions containing styrene-butadiene rubber (SBR) latex polymers, and to methods of making and using polymer-modified asphalt emulsions. Background Art

[0002] Asphalt compositions have a wide range of applications, including but not limited to the production of aggregate pavement. The properties of asphalt can be improved by incorporating styrene-butadiene latex polymers. Styrene-butadiene latex particles need to reverse particle charge, i.e., convert negative charge into positive charge, to be compatible with the cationic surfactant used in the manufacture of cationic asphalt emulsions. In addition, some SBR-modified emulsions have high aggregate losses due to slow asphalt droplet rupture. An asphalt composition having better adhesion, setting time, and viscosity suitable for good workability is needed for aggregate. Compositions and methods described herein meet these and other requirements. Summary of the invention

[0003] Disclosed herein is a composition comprising styrene-butadiene latex. In some embodiments, the polymer comprises styrene and butadiene and is a styrene-butadiene copolymer, such as a non-carboxylated styrene-butadiene copolymer. The composition may be an aqueous dispersion or an emulsion. The composition comprises a styrene-butadiene latex that can be polymerized at high temperatures (e.g., greater than 40°C) or a styrene-butadiene latex that is a blend of a styrene-butadiene latex that is polymerized at high temperatures (e.g., greater than 40°C) and a styrene-butadiene latex that is polymerized at low temperatures (less than 40°C, e.g., 5°C to 25°C). The composition may have a butadiene / styrene monomer weight ratio of 75 / 25. When used in a polymer-modified cationic asphalt emulsion, the styrene-butadiene latex does not require charge reversal. Therefore, the styrene-butadiene latex disclosed herein is significantly more economical than the cationic SBR latex that requires a cationic surfactant to make a cationic asphalt emulsion.

[0004] Also disclosed herein is a composition comprising asphalt and styrene-butadiene latex. The composition may further comprise water and be in the form of a dispersion or emulsion comprising asphalt and styrene-butadiene latex.

[0005] Also disclosed herein are paints, coatings, paper binders or coatings, foams, adhesives, powders, carpet compositions, adhesive layers, and asphalt compositions comprising the compositions disclosed herein. In some embodiments, the asphalt compositions disclosed herein have a significantly higher glass transition temperature than the styrene-butadiene rubber latex used in the cationic asphalt emulsion.

[0006] Also disclosed herein are methods of preparing the compositions disclosed herein. The details of one or more embodiments are set forth in the following description. Other features, objects, and advantages will be apparent from the specification, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1 Particle size and distribution are provided for asphalt emulsions prepared using Examples 2 and 3, where no cationic inverting surfactant was used to impart a positive charge to the latex particles. DETAILED DESCRIPTION

[0008] Disclosed herein are asphalt emulsion compositions comprising styrene-butadiene latex. In some embodiments, the polymer styrene-butadiene latex is derived from styrene in an amount of 90% to 10% by weight (e.g., 90% or less, 85% or less, 80% or less, 75% or less, 70% or less, 65% or less, 60% or less, 55% or less, 45% or more, 40% or more, 35% or more, 30% or more, 25% or more, 20% or more, 15% or more, 10% or more, or in any range encompassed by these endpoints). In some embodiments, the polymer may be derived from butadiene in an amount from 10% to 90% by weight (e.g., 10% or more, 15% or more, 20% or more, 25% or more, 30% or more, 35% or more, 40% or more, 45% or more, 55% or less, 60% or less, 65% or less, 70% or less, 75% or less, 80% or less, 85% or less, 90% or less, or any range encompassed by these endpoints).

[0009] Latex copolymer is non-carboxylated and does not include acid monomer units. Copolymer can be derived from styrene monomer and butadiene monomer only or can be derived from other monomers, i.e., include other monomer units. In some embodiments, copolymer includes 10 weight % or less other monomer units. For example, copolymer can include at least one additional conjugated diene monomer (for example, isoprene) or natural rubber. Copolymer can also include at least one additional vinyl aromatic monomer, such as alpha-methylstyrene or o-chlorostyrene. Other suitable monomers include acrylonitrile, methacrylonitrile, acrylamide and methacrylamide. In some embodiments, one or more additional monomers can include at least one (meth) acrylate. For example, methyl, ethyl, n-butyl, isobutyl and 2-ethylhexyl acrylate and methacrylate can be used.

[0010] Since the copolymer is non-carboxylated and does not contain acid monomer units, the commonly used cationic reversing surfactants used to modify the charge of the copolymer dispersion to be cationic are not necessary. Examples of these cationic reversing surfactants include REDICOTE.RTM.E-5 (Akzo Nobel, Chicago, Ill.), REDICOTE.RTM.E-11 (Akzo Nobel, Chicago, Ill.), REDICOTE.RTM.E-53 (Akzo Nobel, Chicago, Ill.), REDICOTE.RTM.E-606 (Akzo Nobel, Chicago, Ill.), REDICOTE.RTM.E-5127 (Akzo Nobel, Chicago, Ill.), ADOGEN.RTM.477HG (Chemtura Chemical Co., Greenwich, Conn.), and REDICOTE.RTM.E-606 (Akzo Nobel, Chicago, Ill.). Corp., Greenwich, Conn.), INDULIN.RTM.W-1 (MeadWestvaco, Charleston, SC), INDULIN.RTM.W-5 (MeadWestvaco, Charleston, SC), INDULIN.RTM.SBT (MeadWestvaco, Charleston, SC), and INDULIN.RTM.MQK (MeadWestvaco, Charleston, SC), TETRONIC.TM. and PLURONIC.TM. (BASF Corporation), nonylphenol ethoxylates, octylphenol ethoxylates, dodecylphenol ethoxylates, linear alcohol ethoxylates, branched alcohol ethoxylates (such as tridecyl alcohol ethoxylates, alcohol ethoxylates, block copolymers, PEG esters, and castor oil ethoxylates.

[0011] The compositions disclosed herein can be prepared by any polymerization process known in the art. In some embodiments, the compositions disclosed herein are prepared by dispersion, microemulsion or emulsion polymerization. The compositions disclosed herein can be prepared, for example, by using free radical emulsion polymerization to polymerize styrene, butadiene and optionally other monomers. In some embodiments, the polymerization reaction medium is an aqueous medium. Solvents other than water can also be used in the emulsion. Emulsion polymerization can be carried out in an intermittent, semi-intermittent or continuous method. In some embodiments, a portion of the monomers can be heated to the polymerization temperature and partially polymerized, and then the remainder of the polymerization batch can be continuously, step by step or in a superposition of a concentration gradient. The method can use a single reactor or a series of reactors as will be readily understood by those skilled in the art. For example, a review of multiphase polymerization technology is provided in M.Antonelli and K.Tauer, "Macromol.Chem.Phys." 2003, Vol. 204, pp. 207-19.

[0012] Polymer dispersions can be prepared by first charging a reactor with seed latex, water, monomers and optionally at least one nonionic surfactant. Seed latex (although optional) helps initiate polymerization and helps produce polymers with consistent particle size. Any seed latex suitable for a specific monomer reaction can be used, such as polystyrene seed. The initial charge can also include a chelating agent or complexing agent, such as ethylenediaminetetraacetic acid (EDTA). Other compounds such as buffer can be added to the reactor to provide a desired pH for the emulsion polymerization reaction. For example, an alkali or alkaline salt (such as KOH or tetrasodium pyrophosphate) can be used to increase the pH, while an acid or acidic salt can be used to reduce the pH. The initial charge can then be heated to a temperature at or near the reaction temperature. The reaction temperature can be, for example, 5°C to 100°C (for example, 40°C to 90°C, 50°C to 85°C or 55°C to 80°C).

[0013] After the initial charge, the monomer to be used for polymerization can be continuously fed into the reactor in the form of one or more monomer feed streams. The monomer can be supplied as a pre-emulsion in an aqueous medium, particularly if an acrylate monomer is used in the polymerization. The initiator feed stream can also be continuously added to the reactor when the monomer feed stream is added, but if a monomer pre-emulsion is used in the process, it is also possible to expect that at least a portion of the initiator solution will be included in the reactor before adding the monomer pre-emulsion. Monomer and initiator feed streams are usually continuously added to the reactor in a predetermined time period (e.g., 1.5 hours to 15 hours) to cause polymerization of the monomer and thus produce a polymer dispersion. At this point, nonionic surfactants and / or anionic surfactants can be added as a part of monomer stream or initiator feed stream, but these surfactants can be provided in a separate feed stream. In addition, one or more buffers can be included in the monomer stream or initiator feed stream, or provided in a separate feed stream to change or maintain the pH of the reactor.

[0014] The monomers may be fed in one or more feed streams, each of which contains one or more of the monomers used in the polymerization process. For example, styrene and butadiene (when used) may be provided in separate monomer feed streams, or may be added as pre-emulsions. It may also be advantageous to delay the feeding of certain monomers to provide certain polymer properties or to provide a layered or multiphase structure (e.g., a core / shell structure).

[0015] The molecular weight of the copolymer can be adjusted by adding a small amount of molecular weight regulator, for example, 0.01% to 4% by weight based on the monomers being polymerized. Specific regulators that can be used include organic thio compounds (e.g., tert-dodecyl mercaptan), allyl alcohol, and aldehydes.

[0016] The initiator feed stream may include at least one initiator or initiator system for causing polymerization of the monomers in the monomer feed stream. The initiator stream may also include water and other desired components suitable for the monomer reaction to be initiated. The initiator may be any initiator known in the art for emulsion polymerization, such as an azo initiator; ammonium persulfate, potassium persulfate or sodium persulfate; or a redox system, which typically includes an oxidant and a reductant. Commonly used redox initiation systems are described, for example, by ASSarac in Progress in Polymer Science 24, 1149-1204 (1999). Exemplary initiators include aqueous solutions of azo initiators and sodium persulfate. The initiator stream may optionally include one or more buffers or pH adjusters.

[0017] In addition to monomer and initiator, anionic surfactants such as anionic surfactants or nonionic surfactants described herein or nonionic surfactants (i.e., emulsifiers) can be fed into the reactor. Surfactant can be provided in the initial charge of the reactor, provided in the monomer feed stream, provided in the aqueous feed stream, provided in the pre-emulsion, provided in the initiator stream, or its combination. Surfactant can also be provided as a separate continuous flow to the reactor. Based on the gross weight of monomer and surfactant, surfactant can be provided in an amount of 1 % by weight to 5 % by weight. In some embodiments, surfactant is provided in an amount less than 2 % by weight.

[0018] Once polymerization is complete, the polymer dispersion can be chemically stripped to reduce its residual monomer content. This stripping process can include a chemical stripping step and / or a physical stripping step. In some embodiments, the polymer dispersion is chemically stripped by continuously adding an oxidant, such as a peroxide (e.g., tert-butyl hydroperoxide) and a reducing agent (e.g., acetone sodium bisulfite) or another redox pair to a reactor at high temperature for a predetermined period of time (e.g., 0.5 hours). Suitable redox pairs are described by ASSarac in Progress in Polymer Science 24, 1149-1204 (1999). If desired, an optional defoamer can also be added before or during the stripping step. In the physical stripping step, water or steam flushing can be used to further eliminate the unpolymerized monomers in the dispersion. Once the stripping step is completed, the pH of the polymer dispersion can be adjusted, and a biocide or other additives can be added. Cationic, anionic and / or amphoteric surfactants or polyelectrolytes can be optionally added in the final product after the stripping step or later if desired to provide a cationic or anionic polymer dispersion.

[0019] Once the polymerization reaction is complete and the stripping step is completed, the temperature of the reactor can be reduced.

[0020] The styrene-butadiene composition of the present invention may include an additional styrene-butadiene copolymer polymerized at low temperature (e.g., less than 40°C, such as at 5°C to 25°C). The additional styrene-butadiene copolymer may have a styrene to butadiene monomer weight ratio such as the styrene to butadiene monomer weight ratio described above for the high temperature styrene-butadiene copolymer described herein, or may have a styrene to butadiene monomer weight ratio such as the styrene to butadiene monomer weight ratio of the SBR latex. The additional styrene-butadiene copolymer may also include additional monomers, such as the monomers described above for the high temperature styrene-butadiene copolymer described herein. The additional styrene-butadiene copolymer may also include acid monomer units, although low temperature SBR generally does not include acid monomer units. In some examples, the additional styrene-butadiene copolymer may be crosslinked or cured using a sulfur curing agent. The additional styrene-butadiene copolymer may include cis-1,4 butadiene units in an amount less than 20% of the total number of butadiene units in the copolymer and trans-1,4 butadiene units in an amount greater than 60%. The additional styrene-butadiene copolymers may have a higher gel content (e.g., greater than 25%) and may have a soluble portion having a weight average molecular weight greater than 400,000 g / mol, greater than 450,000 g / mol, or greater than 500,000 g / mol as measured by gel permeation chromatography (GPC).

[0021] The styrene-butadiene copolymer of high temperature polymerization can be prepared by polymerizing styrene monomer and butadiene monomer in an aqueous emulsion polymerization reaction at a temperature greater than 40°C, greater than 50°C or greater than 60°C, or at a temperature less than 100°C, less than 90°C or less than 80°C. Continuous, semi-batch (semi-continuous) or intermittent methods can be used to prepare the styrene-butadiene copolymer of high temperature polymerization. In some examples, a continuous method is used to prepare the styrene-butadiene copolymer of high temperature polymerization by continuously feeding one or more monomer streams, surfactant streams and initiator streams to one or more reactors. The monomers in one or more monomer streams can be fed with a desired butadiene to styrene weight ratio. The seed latex can also be first loaded into the reactor. In some embodiments, the polymerization method of the styrene-butadiene copolymer using high temperature polymerization can be prepared using single-stage polymerization (for example, by using a single reactor). In addition, uniform copolymer particles (rather than block copolymers) can be prepared.

[0022] The surfactant stream comprises a surfactant and water and may be mixed with an initiator stream in some embodiments. The surfactant in the emulsion stream may be a synthetic surfactant or a natural surfactant. For example, the surfactant may be a natural surfactant such as sodium oleate or potassium oleate or a sodium or potassium salt of abietic acid. The surfactant may be present in the reactor in an amount of 0.5 wt % to 5 wt % based on the total weight of the monomers.

[0023] At polymerization temperatures of 70° C. or higher, thermal initiators such as ammonium persulfate, potassium persulfate, or sodium persulfate may be used in the reactor. At temperatures less than 70° C., thermal initiators may be mixed with or replaced by redox initiators comprising a free radical generator, a reducing agent, and an activator (e.g., a water-soluble metal salt).

[0024] Suitable free radical generators include organic peroxy compounds such as benzoyl peroxide, hydrogen peroxide, di-tert-butyl peroxide, dicumyl peroxide, 2,4-dichlorobenzoyl peroxide, decanoyl peroxide, lauroyl peroxide, diisopropylbenzene hydroperoxide, cumene hydroperoxide, p-methane hydroperoxide, α-pinene hydroperoxide, tert-butyl hydroperoxide, acetylacetone peroxide, methyl ethyl ketone peroxide, succinic acid peroxide, dihexadecyl peroxide dicarbonate, tert-butyl peracetate, tert-butyl permaleate, tert-butyl perbenzoate, etc.; and alkyl perketals such as 2,2-bis(tert-butyl peroxide) butane, 3,3-bis-(tert-butyl peroxide) ethyl butyrate or 1,1-bis(tert-butyl peroxy) cyclohexane. In some embodiments, the free radical generator includes diisopropylbenzene hydroperoxide or p-methane hydroperoxide. The free radical generator is generally present in an amount between 0.01 wt % and 1 wt % based on the total weight of monomers.

[0025] Suitable reducing agents for the initiator stream include sulfur dioxide; alkali metal disulfites; alkali metal and ammonium bisulfites; thiosulfates, dithionites and formaldehyde sulfoxylates; hydroxylamine hydrochloride; hydrazine sulfate; glucose and ascorbic acid. For example, the reducing agent may include sodium formaldehyde sulfoxylate dihydrate (SFS), sodium metabisulfite, or a mixture thereof. The reducing agent may be present in an amount between 0.01 wt % and 1 wt % based on the total weight of the monomers. In addition, the weight ratio of the reducing agent to the free radical generator may be between 0.2:1 and 1:1.

[0026] The water-soluble metal salt can be an iron salt, a copper salt, a cobalt salt, a nickel salt, a tin salt, a titanium salt, a vanadium salt, a manganese salt, a chromium salt or a silver salt, and can be selected from a variety of water-soluble metal salts. Suitable water-soluble metal salts include copper nitrate (II), copper (II) metaborate, copper (II) bromate, copper (II) bromide, copper (II) bromide, copper perchlorate, copper dichromate (II), copper (II) nitrate (II) hexahydrate, iron (II) acetate, iron (III) bromide, iron (III) bromide hexahydrate, iron (II) perchlorate, iron (III) dichromate, iron (III) formate, iron (III) lactate, iron (III) malate, iron (III) nitrate, iron (III) oxalate, iron (II) sulfate pentahydrate, cobalt (II) acetate, cobalt (II) benzoate, cobalt (II) bromide hexahydrate, cobalt chloride (III), tetrahydrocobalt (II) fluoride, nickel hypophosphite, nickel octoate, tin tartrate, titanium oxalate, vanadium tribromide, silver nitrate and silver fluorosilicate. The metal may also be complexed with a compound such as ethylenediaminetetraacetic acid (EDTA) to increase its solubility in water. For example, an iron / EDTA complex or a cobalt / EDTA complex may be used. The water-soluble metal salt may be present in an amount of less than 0.01 wt % based on the total weight of the monomers.

[0027] The polymerization reaction can be carried out in the presence of a molecular weight regulator to reduce the molecular weight of the copolymer. Suitable molecular weight regulators include C8-C 12 Thiols, such as octyl, nonyl, decyl or dodecanethiol. In some embodiments, tert-dodecyl mercaptan is used as a molecular weight regulator. The amount of tert-dodecyl mercaptan used will depend on the molecular weight required for the copolymer. In some embodiments, based on the total monomer weight, the amount of the molecular weight regulator is 0.01 wt % to 4 wt % (e.g., 0.1 wt % to 1 wt %).

[0028] One or more monomer feeds, surfactant feeds, and initiator feeds may be fed separately into a reactor where polymerization of styrene monomer and butadiene monomer occurs.The polymer content of the styrene-butadiene composition of the present invention may range from 30% to 75%.

[0029] Once the desired conversion level is reached, the polymerization reaction can be terminated by adding a shortstop to the reactor. Shortstops react rapidly with free radicals and oxidants, thereby destroying all remaining initiator and polymer free radicals and preventing the formation of new free radicals. Exemplary shortstops include organic compounds having a quinone-type structure (e.g., quinone) and organic compounds that can be oxidized to a quinone-type structure (e.g., hydroquinone), which are optionally mixed with the following items: water-soluble sulfides (such as hydrogen sulfide, ammonium sulfide, or sulfides or hydrosulfides of alkali metals or alkaline earth metals); N-substituted dithiocarbamates; reaction products of alkylene polyamines with sulfur, presumably containing sulfides, disulfides, polysulfides and / or mixtures of these and other compounds; dialkylhydroxylamines; N,N'-dialkyl-N,N'-methylenebishydroxylamines; dinitrochlorobenzene; dihydroxydiphenyl sulfide; dinitrophenylbenzothiazole sulfide; and mixtures thereof. In some embodiments, the shortstop is hydroquinone or potassium dimethyldithiocarbamate. The shortstop may be added in an amount between 0.01 wt % and 0.1 wt % based on the total weight of the monomers. However, the high temperature polymerization may be allowed to proceed until complete monomer conversion, i.e., greater than 99%, in which case a shortstop may not be employed.

[0030] As mentioned above, the styrene-butadiene copolymer of high temperature polymerization can also be prepared using a batch process. In a batch process, monomers, surfactants, free radical generators and water are all added to a reactor and stirred. After reaching the desired polymerization temperature, an activator solution containing a reducing agent and a water-soluble metal salt (if necessary) can be added to initiate polymerization, if necessary.

[0031] If a semi-batch process is used, the monomers, the surfactant in the aqueous solution, and the free radical generator in the aqueous solution are all fed to the reactor within a period of time (usually 3 hours to 20 hours). If necessary, an activator solution containing a reducing agent and / or a water-soluble metal salt may also be added to the reactor before starting other feeds, or it may be fed to the reactor within a time interval. The high temperature polymerized styrene-butadiene copolymer is preferably allowed to complete monomer conversion, i.e., greater than 99%, in which case a shortstop may not be used. However, if desired, if the desired conversion is less than 99%, a shortstop may be added to terminate the polymerization.

[0032] Once the polymerization is terminated (in a continuous, semi-batch or batch process), unreacted monomers may be removed from the latex dispersion. For example, butadiene monomer may be removed by flash distillation at atmospheric pressure and then under reduced pressure. Styrene monomer may be removed by steam stripping in a tower.

[0033] Additional styrene-butadiene latex can be an SBR copolymer dispersion, which can be agglomerated, for example, using chemical agglomeration, frozen agglomeration or pressure agglomeration, and remove water to produce a solid content greater than 50% to 75%. In some embodiments, the solid content is 55% or greater, 60% or greater or 65% or greater. As mentioned above, the high temperature styrene-butadiene copolymer dispersion can be blended with the additional SBR copolymer dispersion before agglomeration. Agglomerated particles cause polymer dispersions with larger particles of wider particle size distribution. Agglomerated particles as described herein have a particle size of 100nm to 5nm. For example, the particle size can be in the range of 100nm to 2nm or 200nm to 1nm.

[0034] Even once concentrated, the co-agglomerated dispersion may have a viscosity that allows it to flow readily (ie, it does not gel).For example, an aqueous dispersion having a solids content greater than 60% may have a viscosity of less than 1000 cp at 20°C.

[0035] An antioxidant may be additionally added to the styrene-butadiene latex composition SBR latex dispersion to prevent oxidation of the double bonds of the SBR polymer, and may be added before or after the vulcanization of the SBR latex. The antioxidant may be a substituted phenol or a secondary aromatic amine.

[0036] Exemplary substituted phenols include 2,6-di-tert-butyl-p-cresol (DBT); 4,4'-thiobis(6-tert-butyl-m-cresol); 3-tert-butyl-4-hydroxyanisole (3-BHT); 2-tert-butyl-4-hydroxyanisole (2-BHT); 2,2-methylenebis(4-methyl-6-tert-butylphenol) (MBMBP); 2,2-methylenebis(4-ethyl-6-tert-butylphenol) (MBEBP); 4,4-butylenebis(3-methyl-6-tert-butylphenol) (SBMBP); 2,2-ethylenebis(4,6-di-tert-butylphenol); 2,6-di-tert-butyl-4-sec-butylphenol; styrenated phenol; styrenated p-cresol; 1,1,3-tris(2-methyl-4-hydroxy-5 -tert-butylphenol) butane; tetrakis[methylene-3-(3,5-di-tert-butyl-4-hydroxyphenol) propionate]methane; n-octadecyl-3-(4-hydroxy-3,5-di-tert-butylphenyl) propionate; triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxy-phenyl) propionate]; 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene; 2,2'-dihydroxy-3,3'-di(α-methylcyclohexyl)-5,5'-dimethyldiphenylmethane; 4,4-methylenebis(2,6-di-tert-butylphenol); tris(3,5-di-tert-butyl-4-hydroxyphenol); tris(3,5-di-tert-butyl-4-hydroxyphenyl) isocyanurate; 1,3,5-tris(3 ',5'-di-tert-butyl-4-hydroxybenzoyl) isocyanurate; bis[2-methyl-4-(3-n-alkylthiopropionyloxy)-5-tert-butylphenyl] sulfide; 1-oxy-3-methylisopropylbenzene; 2,5-dibutylhydroquinone; 2,2'-methylenebis(4-methyl-6-nonylphenol); alkylated bisphenol; 2,5-di-tert-amylhydroquinone; polybutyrated bisphenol-A; bisphenol-A; 2,6-di-tert-butyl-p-ethylphenol; 2,6-bis(2'-hydroxy-3-tert-butyl-5'-methylbenzyl)-4-methylphenol; 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl) isocyanurate; terephthaloyl-bis(2,6-dimethyl-4-tert-butyl-3-hydroxybenzyl) sulfide); 2,6-tert-butylphenol; 2,6-di-tert-butyl-2-dimethylamino-p-cresol; 2,2'-methylenebis(4-methyl-6-cyclohexylphenol); hexamethylene glycol bis(3,5-tert-butyl-4-hydroxyphenyl) propionate; (4-hydroxy-3,5-di-tert-butylanilino)-2,6-bis(octylthio)-1,3,5-triazine; 2,2-thio[diethyl-bis-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]; N,N'-hexamethylene(3,5-di-tert-butyl-4-hydroxycinnamic acid); 3,5-di-tert-butyl-4-hydroxybenzyl diethyl phosphate; 2,4-dimethyl-6-tert-butylphenol; 4,4'-methylenebis(2,6-di-tert-butylphenol);4,4'-thiobis(2-methyl-6-tert-butylphenol); tris[2-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxyethyl]isocyanurate; 2,4,6-tributylphenol; bis[3,3-bis(4'-hydroxy-3'-tert-butylphenyl)butyric acid]diol ester; 4-hydroxymethyl-2,6-di-tert-butylphenol; and bis(3-methyl-4-hydroxy-5-tert-butylbenzyl)sulfide. Exemplary secondary aromatic amines include N-phenyl-N'-isopropyl-p-phenylenediamine; N-phenyl N'-(1,3-dimethylbutyl)-p-phenylenediamine; N,N'-diphenyl-p-phenylenediamine; dioctyl-diphenylamine; di(β-naphthyl)p-phenylenediamine; 2,2,4-trimethyl-1,2-dihydroquinoline polymers and diaryl-p-phenylenediamine. In addition, sulfur-containing antioxidants such as dilauryl thiodipropionate, distearyl thiodipropionate, and 2-mercapto-benzimidazole can be used; phosphorus-containing antioxidants such as distearyl pentaerythritol diphosphite; nickel-containing antioxidants such as nickel diisobutyldithiocarbamate, nickel dimethyldithiocarbamate, and nickel di-n-butyldithiocarbamate; 2-mercaptobenzimidazole; 2-mercaptobenzimidazole zinc; and 1,11-(3,6,9-trioxaundecyl)bis-3-(dodecylthio)propionate. The antioxidant can be provided in an amount of 0.1 wt % to 5.0 wt % or 0.5 wt % to 2.0 wt % based on the weight of the SBR copolymer. ;

[0037] Antiozonants may also be added to the SBR copolymer dispersion to prevent atmospheric ozone from cleaving the SBR by cleaving the double bonds of the SBR polymer. Typical antiozonants include waxes (e.g., commercially available from RT Vanderbilt Co. H) and N,N'-alkylaryl, N,N'-dialkyl and N,N'-diaryl derivatives of p-phenylenediamine, such as N,N'-di(2-octyl)-p-phenylenediamine, N,N'-di-3(5-methylheptyl)-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine and N-cyclohexyl-N'-phenyl-p-phenylenediamine. The antiozonant may be provided in an amount of 0.5 wt % to 10 wt %, 1 wt % to 5 wt % or 1.5 wt % to 3 wt % based on the weight of the SBR copolymer.

[0038] Pre-vulcanization inhibitors may also be added to the SBR dispersion to prevent premature vulcanization or scorching of the SBR polymer. For example, N-cyclohexylthiophthalimide; phthalic anhydride; N-cyclohexylthiophthalimide; N-phenyl-N-(trichloromethylsulfinyl)-benzenesulfonamide; bis-(sulfonylamino)-sulfide or polysulfide (e.g., bis-(N-methyl-p-toluenesulfonylamino)-disulfide); substituted thiophosphoramides (e.g., N-cyclohexylthio-N-phenyldiethylphosphoramide); N-(sulfinyl)methacrylamide; thiosubstituted-1,3,5-triazines, -diamines or -triamines; 2-(thioamino)-4,6-diamino-1,3,5-triazine; N,N'-substituted bis-(2,4-diamino-s-triazin-6-yl)-low sulfide; and substituted thioformamidines can be used as pre-curing inhibitors. In some embodiments, the pre-curing inhibitor is N-cyclohexylthio-phthalimide (commercially available from Flexsys). PVI) or N-phenyl-N-(trichloromethylsulfinyl)benzenesulfonamide (commercially available from Bayer E) The pre-vulcanization inhibitor is typically provided in an amount of 1 to 5 wt % or 1.5 to 3 wt % based on the weight of the SBR polymer.

[0039] Typically in the presence of a vulcanizing agent, a vulcanization accelerator, an anti-reversion agent and optionally a cross-linking agent, SBR dispersions can be vulcanized or cured by heating SBR to crosslink with SBR polymers, thereby increasing the tensile strength and elongation of rubber. Exemplary vulcanizing agents include various sulfurs, such as sulfur powder, precipitated sulfur, colloidal sulfur, insoluble sulfur and highly dispersible sulfur; sulfur halides, such as sulfur monochloride, sulfur dichloride; sulfur donors, such as 4,4'-dithiodimorpholine; selenium; tellurium; organic peroxides, such as dicumyl peroxide, di-tert-butyl peroxide; quinone dioximes, such as p-quinone dioxime and p, p'-dibenzoylquinone dioxime; organic polyamine compounds, such as triethylenetetramine, hexamethylenediamine carbamate, 4,4'-methylenebis(cyclohexylamine) carbamate, 4,4'-methylenebis-o-chloroaniline; alkylphenol resins with methylol groups; and mixtures thereof. In certain embodiments, vulcanizing agents include sulfur dispersions or sulfur donors. The vulcanizing agent may be present at 0.1 wt % to 15 wt %, 0.3 wt % to 10 wt %, or 0.5 wt % to 5 wt %, based on the weight of the SBR polymer.

[0040] Exemplary vulcanization accelerators include sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazole sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, N-oxydiethylene-2-benzothiazole sulfenamide, N-oxydiethylenethiocarbamoyl-N-oxydiethylenesulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; guanidine-based vulcanization accelerators such as diphenylguanidine, di-o-tolylguanidine, and di-o-tolylbiguanidine; thiourea-based vulcanization accelerators such as thiocarboxylic acid; Aniline, di-o-toluenethiourea, ethylenethiourea, diethylenethiourea, dibutylthiourea, trimethylthiourea, etc.; thiazole vulcanization accelerators such as 2-mercaptobenzothiazole, dibenzothiazole disulfide, 2-mercaptobenzothiazole zinc salt, 2-mercaptobenzothiazole sodium salt, 2-mercaptobenzothiazole cyclohexylamine salt, 4-morpholinyl-2-benzothiazole disulfide and 2-(2,4-dinitrophenylthio)benzothiazole; thiadiazine vulcanization accelerators such as activated thiadiazine; thiuram vulcanization accelerators such as tetramethylthiuram monosulfide, tetramethylthiuram disulfide, tetraethylthiuram disulfide, tetrathiophene Butylthiuram and dipentamethylenethiuram tetrasulfide; dithiocarbamate vulcanization accelerators such as sodium dimethyldithiocarbamate, sodium diethyldithiocarbamate, sodium di-n-butyldithiocarbamate, lead dimethyldithiocarbamate, lead diamyldithiocarbamate, zinc diamyldithiocarbamate, zinc dimethyldithiocarbamate, zinc diethyldithiocarbamate, zinc di-n-butyldithiocarbamate, zinc pentamethylenedithiocarbamate, zinc ethylphenyldithiocarbamate, tellurium diethyldithiocarbamate, bismuth dimethyldithiocarbamate, dimethyl dithiocarbamate The present invention also includes the following: the vulcanization accelerators: selenium dithiocarbamate, selenium diethyl dithiocarbamate, cadmium diethyl dithiocarbamate, copper dimethyl dithiocarbamate, iron dimethyl dithiocarbamate, diethylamine diethyl dithiocarbamate, piperidinium pentamethylene dithiocarbamate, and piperidinium pentamethylene dithiocarbamate; xanthate-based vulcanization accelerators such as sodium isopropyl xanthate, zinc isopropyl xanthate, and zinc butyl xanthate; isophthalate-based vulcanization accelerators such as dimethyl ammonium hydrogen isophthalate; aldehyde-amine-based vulcanization accelerators such as butyraldehyde-amine condensation products and butyraldehyde-monobutylamine condensation products; and mixtures thereof. Based on the weight of the SBR polymer, the vulcanization accelerator may be present in the range of 0.1 wt % to 15 wt %, 0.3 wt % to 10 wt %, or 0.5 wt % to 5 wt %.

[0041] Anti-reversion agents may also be included in the vulcanization system to prevent reversion, i.e., an undesirable decrease in crosslink density. Suitable anti-reversion agents include zinc salts of aliphatic carboxylic acids, zinc salts of monocyclic aromatic acids, bismaleimides, biscitraconimides, bis-siconimides, aromatic biscitraconamide acids, bis-succinimides, and polymeric bis-succinimidyl polysulfides (e.g., N,N'-xylene dicyclic amides). Based on the weight of the SBR polymer, the anti-reversion agent may be present in the range of 0 wt % to 5 wt %, 0.1 wt % to 3 wt %, or 0.1 wt % to 2 wt %.

[0042] The above-mentioned additives (antioxidant, antiozonant, pre-vulcanization inhibitor, vulcanizing agent, vulcanization accelerator and anti-reversion agent) can be mixed with SBR latex dispersion. Crosslinking agent can also be included in the vulcanization system on a small scale to promote the crosslinking of SBR polymer chains, and is typically an organic peroxide. SBR latex dispersion can be vulcanized under elevated temperature and pressure, and vulcanization process is well known to those skilled in the art.

[0043] As described above, a high temperature polymerized styrene-butadiene copolymer dispersion can be blended with a low temperature polymerized styrene-butadiene copolymer dispersion prepared at a temperature below 40° C. (e.g., 5° C. to 25° C.). It is noted that the low temperature polymerized styrene-butadiene copolymer dispersion can be prepared using the method described above for the high temperature polymerized styrene-butadiene copolymer dispersion, except that it is prepared at a lower temperature.

[0044] High temperature styrene-butadiene copolymers and dispersions thereof can be used in various applications. For example, high temperature styrene-butadiene copolymers can be used in vehicle tires, carpet backings, adhesives, foams, and paper coatings. In some embodiments, high temperature styrene-butadiene copolymers are used as the sole styrene-butadiene polymer composition in asphalt-based systems such as hot mix asphalt and asphalt emulsions.

[0045] In some embodiments, high temperature styrene-butadiene copolymers can be used in hot mix asphalt formulations. Polymer-modified hot mix asphalt can be prepared, for example, by blending asphalt and an aqueous dispersion of a high temperature polymerized styrene-butadiene copolymer at a blending temperature exceeding the boiling point of water. For example, the blending temperature can be 150°C or higher, or 160°C or higher. The high temperature polymerized styrene-butadiene copolymer can be blended with a second styrene-butadiene copolymer as discussed herein. The polymer-modified hot mix asphalt composition is substantially free of water and can have a viscosity of, for example, 3000cp or less, less than 2000cp or less than 1500cp at 135°C. In some embodiments, adding a high temperature styrene-butadiene copolymer alone or in a blend with the SBR latex of the present invention to a hot mix asphalt composition can result in a viscosity increase of less than 125%, less than 100%, less than 75% or less than 50%. Based on the total solid content of the styrene-butadiene copolymer and asphalt, the styrene-butadiene copolymer can be present in an amount of 0.5% to 30%. For example, the copolymer may be present in an amount of 1% or more, 1.5% or more, 2% or more, 2.5% or more, or 3% or more, or may be present in an amount of 25% or less, 20% or less, 15% or less, 10% or less, 7.5% or less, or 5% or less. In some embodiments, when the polymer-modified hot mix asphalt composition comprises 3% or more of the copolymer (e.g., 3.5%, 4%, 4.5%, 5%, 5.5%, or 6%), its viscosity at 135°C may be less than 3000cp. In addition, the copolymers described herein have the possibility of imparting a controllable viscosity to hot asphalt (e.g., at 135°C) up to a level of 20wt.% latex polymer. As noted herein, high temperature polymerized styrene-butadiene copolymers may be cured prior to blending with asphalt. In some embodiments, high temperature polymerized styrene-butadiene copolymers may be blended with asphalt and then cured. The polymer-modified hot mix asphalt formulation may be used for paving to produce pavement or may be used in asphalt shingles.

[0046] In some embodiments, high temperature styrene-butadiene copolymer can be used in asphalt emulsion.Polymer modified asphalt emulsion comprises asphalt and styrene-butadiene copolymer dispersed in water with surfactant.Polymer modified asphalt emulsion can be prepared by providing aqueous asphalt emulsion and mixing asphalt emulsion with aqueous dispersion of high temperature styrene-butadiene copolymer.In some embodiments, aqueous dispersion can further comprise second styrene-butadiene copolymer as described herein.Second styrene-butadiene copolymer can be styrene-butadiene copolymer polymerized at low temperature (e.g., less than 40°C, e.g., at 5°C to 25°C), and can have styrene to butadiene ratio of 20 / 80 to 80 / 20.In some embodiments, aqueous dispersion of styrene-butadiene copolymer (optionally comprising second styrene-butadiene copolymer) can be agglomerated to increase solid content.Based on the total solid content of styrene-butadiene copolymer and asphalt, styrene-butadiene copolymer can be present in an amount of 0.5% to 30%. For example, the copolymer may be present in an amount of 1% or more, 1.5% or more, 2% or more, or 2.5% or more, or may be present in an amount of 25% or less, 20% or less, 15% or less, 10% or less, 7.5% or less, or 5% or less. The resulting asphalt emulsion may be used, for example, to maintain paved asphalt pavement by employing various surface treatments, including micro-surface treatments.

[0047] In some embodiments, the polymer comprising styrene-butadiene rubber latex is in the form of a polymer dispersion having particles having a volume average particle size of 20nm to 500nm (e.g., 40nm to 480nm, 60nm to 460nm, 80nm to 440nm, 100nm to 420nm, 120nm to 400nm, 140nm to 380nm, 160nm to 360nm, 180nm to 340nm, 200nm to 320nm, or 220nm to 300nm, or 240nm to 280nm). In some embodiments, the polymer particles of the obtained polymer dispersion have a number average particle size of 20nm to 300nm (e.g., 30nm to 290nm, 40nm to 280nm, 50nm to 270nm, 60nm to 260nm, 70nm to 250nm, 80nm to 240nm, 90nm to 230nm, 100nm to 220nm, 110nm to 210nm, 120nm to 200nm, 130nm to 190nm or 140nm to 180nm). Use the Nicomp Model 380 purchased from PSS Particle Sizing Systems (Santa Barbara, CA), dynamic light scattering is used to measure particle size. Polymer dispersion can be prepared as a dispersion comprising copolymer particles dispersed in water as a dispersed phase. A polymer dispersion having a total solids content of 5% to 90% by weight (e.g., 10% to 80%, 20% to 70%, 25% to 65%, 35% to 60%, or 45% to 55%) can be prepared. In some embodiments, the polymer dispersion can have a total solids content of 50% by weight or greater (e.g., 50% by weight or greater to 90% by weight or less). In some embodiments, the copolymer dispersion can be spray dried to produce a powder.

[0048] The composition may include one or more surfactants (emulsifiers), such as nonionic surfactants, anionic surfactants, cationic surfactants, amphoteric surfactants or mixtures thereof. Suitable nonionic surfactants include, but are not limited to, polyoxyalkylene alkyl ethers and polyoxyalkylene alkylphenyl ethers (e.g., diethylene glycol monoethyl ether, diethylene glycol diethyl ether, polyoxyethylene lauryl ether, polyoxyethylene stearyl ether and polyoxyethylene nonylphenyl ether); oxyethylene-oxypropylene block copolymers; sorbitan fatty acid esters (e.g., commercially available under the trade name Sorbitan monolaurate purchased from Merck Schuchardt OHG, sold under the trade name Sorbitan monooleate purchased from Merck Schuchat OHG and sold under the trade name Sorbitan trioleate purchased from Merck Schuchardt OHG); Polyoxyethylene sorbitan fatty acid esters (e.g., under the trade name and Polyoxyethylene sorbitan monolaurate purchased from Uniqema; under the trade name Polyoxyethylene sorbitan monopalmitate purchased from Uniqema; under the trade name and Polyoxyethylene sorbitan monostearate purchased from Uniqema; under the trade name and Polyoxyethylene sorbitan monooleate purchased from Uniqema; and under the trade name Polyoxyethylene sorbitan trioleate purchased from Uniqema); Polyoxyethylene sorbitol fatty acid esters (e.g., polyoxyethylene sorbitol tetraoleate); Glycerol fatty acid esters (e.g., glyceryl oleate); Polyoxyethylene glycerol fatty acid esters (e.g., polyoxyethylene glycerol monostearate and polyoxyethylene glycerol monooleate); Polyoxyethylene fatty acid esters (e.g., polyethylene glycol monolaurate and polyethylene glycol monooleate); Polyoxyethylene alkylamines; and Acetylene glycols. In some embodiments, the nonionic surfactant can have an HLB (hydrophilic-lipophilic balance) at room temperature such that 8 < HLB < 15. In some embodiments, the HLB is 14 or less. In some embodiments, the nonionic surfactant comprises ethylene oxide (EO) m and / or propylene oxide (PO) n adducts, where (m + n) ≤ 14, (m + n) ≤ 12, or (m + n) ≤ 10 (e.g., 6 ≤ (m + n) ≤ 10), such as those available under the LUTENSOL TM trademark from BASF.

[0049] Suitable anionic emulsifiers include, but are not limited to, fatty acids, alkyl sulfates, alkyl ether sulfates, alkyl benzene sulfonic acids, alkyl phosphates or their salts, sucrose esters, and mixtures thereof. Anionic polyelectrolytes such as tartrates, borates, oxalates, and phosphates can also be used in the composition. Other suitable anionic surfactants and polyelectrolytes include, but are not limited to, M28B and other anionic surfactants available under the trademark from West Pharmaceutical Services (such as and and anionic surfactants available under the trademark from Akzo Nobel (such as and and lignin sulfonates, such as MARASPERSE TM Those available under trademarks (such as MARASPERSE TM CBOS-3 and MARASPERSE TM N22). In some embodiments, the emulsifier comprises an anionic fatty acid based emulsifier.

[0050] Cationic emulsifiers can be classified as cationic rapid setting (CRS) emulsifiers, cationic quick setting (CQS) emulsifiers, cationic medium setting (CMS) emulsifiers or cationic slow setting (CSS) emulsifiers, and these classifications are known in the art and can be easily measured in emulsions as described in ASTM D977 and D2397. In some embodiments, cationic polyelectrolytes can be provided in the composition. Suitable cationic emulsifiers and polyelectrolytes include alkylamine salts, quaternary ammonium salts, Cationic surfactants (such as and by and Cationic surfactants (such as and Purchased from Kao Specialties Americas Purchased from Cytec Industries Polyethyleneimine such as Trademarks purchased from BASF (such as and ) and polyvinyl amines such as Trademarks purchased from BASF (such as and ). Other suitable cationic polyelectrolytes and surfactants include those listed in, for example, US Pat. Nos. 5,096,495, 5,160,453, and 5,443,632. In some embodiments, the cationic emulsifier includes an amine-based emulsifier.

[0051] Suitable amphoteric surfactants include, but are not limited to, betaine acetate, amidobetaine, sulfobetaine, imidazolium betaine, and amine oxide. Exemplary amphoteric surfactants are E-7000 surfactant, which is available from Akzo Nobel. Suitable anionic emulsifiers include fatty acids, alkyl sulfates, alkyl ether sulfates, alkyl benzene sulfonic acids, alkyl phosphoric acids or their salts, sucrose esters, and mixtures thereof. Anionic polyelectrolytes such as tartrates, borates, oxalates, and phosphates may also be used in the composition. Other suitable anionic surfactants and polyelectrolytes include, but are not limited to, M28B and Other anionic surfactants (such as and );by Anionic surfactants (such as and ); and lignin sulfonates, such as MARASPERSE TM Those available under trademarks (such as MARASPERSE TM CBOS-3 and MARASPERSE TM N22). In some embodiments, the emulsifier comprises an anionic fatty acid based emulsifier.

[0052] Some formulations for the applications disclosed herein include solvents such as water to disperse or emulsify polymers and / or asphalt. Some compositions disclosed herein include water. In some embodiments, the composition includes asphalt and the asphalt includes water and is an aqueous emulsion. In some embodiments, the composition includes a polymer and the polymer includes water and is an aqueous dispersion. In some embodiments, the asphalt and / or polymer include water, and one or both are aqueous dispersions or emulsions. Some formulations for the applications disclosed herein do not include water, but include non-aqueous solvents. Some compositions disclosed herein do not include water. In some embodiments, the polymer and / or asphalt may be in the form of a non-aqueous dispersion or emulsion.

[0053] The composition may also include aggregate. As will be appreciated by those skilled in the art, the aggregate may be of different sizes. Any aggregate conventionally used to produce asphalt paving compositions may be used, including dense-graded aggregate, gap-graded aggregate, open-graded aggregate, recycled asphalt pavement, and mixtures thereof. Dense-graded aggregate exhibits the largest mineral surface area (per unit aggregate). Open-graded aggregate is composed primarily of single, large-sized (e.g., about 0.375 inches to 1.0 inches) stones having very low levels (e.g., less than about two percent of the total aggregate) of fines (e.g., less than 0.25 inches of material) or fillers (e.g., less than 0.075 mm of mineral material). Gap-graded aggregate is between dense-graded aggregate and open-graded aggregate. Recycled asphalt pavement (RAP) materials typically reflect the gradation of the pavement from which the recycled material was obtained. If the original pavement is a dense-graded mix, RAP will also be dense-graded, but it is often observed that the filler content is below the design limit of the original aggregate specification. The aggregate may be applied in an amount of 100 to 2000 parts by weight.

[0054] In some embodiments, the composition comprising aggregates may also comprise air voids. The air voids may be present in an amount of 2 volume % to 30 volume % (eg, greater than 2 volume % to 10 volume %).

[0055] The asphalt composition can be prepared by mixing asphalt, any aromatic recycling agent or non-asphalt rosin material, ion crosslinking agent, emulsifier, acid or alkali, water and any additive and a polymer optionally derived from styrene-butadiene rubber latex. In some embodiments, the polymer is not crosslinked by the ion crosslinking agent, and can be added to the asphalt composition separately from the ion crosslinking agent, and once the water is substantially evaporated, the polymer and the asphalt can be crosslinked by the ion crosslinking agent in the asphalt composition. For example, the asphalt composition can include the ion crosslinking agent, and other components can be added to or included in the composition. For example, the asphalt composition can be an emulsion comprising asphalt and the ion crosslinking agent. In some embodiments, a composition comprising asphalt and the ion crosslinking agent can be provided, and the polymer (for example, as an aqueous dispersion) can be mixed with the composition, and once the water is substantially evaporated, the polymer and the asphalt can be crosslinked with the ion crosslinking agent, thereby producing an asphalt-based composition comprising a crosslinked polymer.

[0056] The specific components can be mixed together by methods known in the art. As mentioned previously, the specific components can be mixed together in any order. In some embodiments, before mixing the asphalt and the acid or alkali with the emulsifier and the polymer, the polymer derived from the styrene-butadiene rubber latex is premixed with an anionic emulsifier or a cationic emulsifier to produce a charged polymer. In some embodiments, the polymer derived from the styrene-butadiene rubber latex is not premixed with any anionic emulsifier or cationic emulsifier to produce a charged latex polymer before mixing the asphalt, acid or alkali with the emulsifier in the soap tank for the emulsion manufacturing system. If the aggregate is blended into the asphalt composition, the aggregate can be added, for example, after blending the other components. In some embodiments, the asphalt composition is prepared at an elevated temperature, such as 160°C to 200°C (hot mix asphalt), 120°C to 160°C (warm mix asphalt) or at a temperature below 120°C (e.g., 5°C to 60°C or 5°C to 90°C). In some embodiments, the asphalt composition can be prepared at ambient temperature.

[0057] Asphalt compositions can be used for pavement or paved surfaces. Pavement surfaces or paved surfaces are hard surfaces capable of carrying pedestrians or vehicles, and may include surfaces such as highways / roads, parking lots, bridges / overpasses, runways, lanes, vehicle paths, running paths, walkways, etc. Asphalt compositions can be applied directly to existing paved surfaces, or can be applied to unpaved surfaces. In some embodiments, the composition is applied to an existing paved layer as a tie layer, and a new layer (such as a hot mix layer) comprising asphalt is applied to the tie layer. The asphalt composition can be applied to a "cold" surface, i.e., a surface with a temperature below 40°C, or can be applied to a high temperature (e.g., 50°C to 120°C, 55°C to 100°C, or 60°C to 80°C) surface.

[0058] In some embodiments, the aggregate is blended into the asphalt composition before application to the surface. In some embodiments, the aggregate is applied to the composition after application to the surface. In some embodiments, sand can be applied to the composition after application to the surface, for example if the composition is to be used as an adhesion layer, to reduce the tackiness of the surface. As will be appreciated by those skilled in the art, the composition and optionally the aggregate can be compacted after application to the surface.

[0059] In some embodiments, the composition is used as an adhesion layer or coating. The adhesion layer is a very light spray application of a diluted asphalt emulsion that can be used to promote adhesion between an existing surface and a new asphalt application. The adhesion layer plays a role in providing a certain degree of adhesion or adhesion between asphalt layers, and in some cases, the layers can be melted together. The adhesion layer also plays a role in reducing the slippage and sliding of the layer relative to other layers in the pavement structure during use or due to the wear and weathering of the pavement structure. As mentioned above, the composition can be applied to an existing paving layer (such as a hot mix layer) as a bonding layer, and a new layer (such as a hot mix layer) including asphalt can be applied to the adhesion layer. As will be understood by those skilled in the art, the adhesion layer does not usually include aggregate, but sand can be applied to the adhesion layer after the application as mentioned above. The composition described herein is unexpectedly found to be a low-track (low-tracking) or "trackless" coating, so that after the adhesion coating is cured, a paving vehicle or other vehicle can be allowed to pass over the coating, so that the vehicle tire or tread is adhered to the coating with a limited amount (low-track) or not at all (trackless). For example, under higher pavement temperatures (50°C to 60°C) and / or with low or medium pen asphalt having a pen value greater than 40dmm, the compositions described herein are unexpectedly found to be low-track or "trackless". The adhesion layer is viscous and is capable of bonding the layers of the pavement structure together under ambient conditions for pavement construction or at elevated temperatures (e.g., as discussed above, up to 140°C). In fact, the adhesion layer provides sufficiently flexible asphalt at low temperatures, and the asphalt has sufficient bonding strength to bond adjacent asphalt layers. The adhesion layer cures quickly, so that the pavement layer can be applied to the coating a few hours to a few days after the emulsion is applied to the substrate. The applied composition can cure within 15 minutes to 45 minutes, and can be cured quickly for 5 minutes to 15 minutes after the composition is applied to the exposed surface. The curing rate will depend on the application rate, the dilution rate used, the base course condition, weather and other similar considerations. If the prepared pavement surface or base course contains excessive moisture, the curing time of the emulsion may be increased.

[0060] In some embodiments, the composition may also be used as a fog seal. A fog seal is a surface treatment that applies a light application of the composition to an existing paved surface, such as a parking lot, to provide an enriched pavement surface that appears new and black. In some embodiments, the fog seal will contain fillers such as carbon black to darken the composition. As will be appreciated by those skilled in the art, the fog seal may not contain aggregate. The fog seal composition, like the bond coat composition, has also been demonstrated as a low-track or "trackless" coating.

[0061] In some embodiments for the adhesion layer and the fog seal layer, the asphalt may be present in an amount of 58 to 62 parts by weight, the polymer comprising styrene-butadiene rubber latex may be present in an amount of 0 to 6 parts by weight, the emulsifier may be present in an amount of 0.75 to 3 parts by weight, the acid or base may be present in an amount of 0.75 to 3 parts by weight, any optional additives may be provided in an amount of up to 5 parts by weight, and water may be present in an amount of 30 to 40 parts by weight. In some embodiments, the composition may be further diluted with water. The composition may be diluted in an amount of 0.05 gallons / yd. 2 Up to 0.10 gallons / yd 2 Apply at a rate of .

[0062] In some embodiments, the composition can be used as a chip seal composition. Chip seal is the most common surface treatment for low traffic roads. The chip seal composition can be applied to the surface and then the aggregate is applied. In some embodiments for chip seal, asphalt can be present in an amount of 64 to 67 parts by weight, a polymer comprising styrene-butadiene rubber latex can be present in an amount of 0 to 3.5 parts by weight, an emulsifier can be present in an amount of 0.15 to 0.35 parts by weight, an acid or base can be present in an amount of 0.15 to 0.35 parts by weight, any optional additives can be provided in an amount of up to 5 parts by weight, and water can be present in an amount of 30 to 40 parts by weight. Aggregate can be provided in an amount of 200 to 1000 parts by weight.

[0063] In some embodiments, the composition can be used as a microsurfacing application. Microsurfacing is designed to achieve rapid traffic recovery and has the ability to handle high traffic roads. For microsurfacing compositions, aggregate can be mixed with asphalt, optionally a polymer comprising styrene-butadiene rubber latex, an emulsifier, and an acid or alkali before being applied to the surface. In some embodiments for microsurfacing, asphalt can be present in an amount of 60 to 62 parts by weight, the polymer comprising styrene-butadiene rubber latex can be present in an amount of 0 to 4.5 parts by weight, an emulsifier can be present in an amount of 0.5 to 2.5 parts by weight, an acid or alkali can be present in an amount of 0.5 to 2.5 parts by weight, any optional additive can be provided in an amount of up to 5 parts by weight (e.g., 0.25 to 2 parts by weight of one or more inorganic salts or up to 5 parts by weight of mineral fillers), and water can be present in an amount of 30 to 40 parts by weight. Aggregate can be provided in an amount of 500 to 2000 parts by weight.

[0064] The paved surface layer obtained using the composition, once dried, also contains the components provided in the composition, except water. Thus, the paved surface layer may contain asphalt in an amount of 40 to 70 parts by weight, a polymer containing styrene-butadiene rubber latex in an amount of 0 to 10 parts by weight, an emulsifier in an amount of 0.1 to 4 parts by weight, and an acid or base in an amount of 0.1 to 4 parts by weight. In terms of the adhesion layer, the paved surface may include: a first layer, the first layer containing asphalt; a bonding layer, the bonding layer is disposed on the first layer and contains asphalt in an amount of 40 to 70 parts by weight, a polymer containing styrene-butadiene rubber latex in an amount of 0 to 10 parts by weight, an emulsifier in an amount of 0.1 to 4 parts by weight, and an acid or base in an amount of 0.1 to 4 parts by weight; and a second layer, the second layer containing asphalt and disposed on the bonding layer.

[0065] Although parts by weight are used for the compositions described herein, weight percentages can be used interchangeably with parts by weight, for example where the composition comprises asphalt, an optional polymer comprising styrene-butadiene rubber latex, an emulsifier, an acid or base, water, and any additives other than aggregate. For example, a composition can be described as comprising: (a) asphalt in an amount of 40% to 70% by weight; (b) a polymer comprising styrene-butadiene rubber latex in an amount of 0% to 10% by weight; (c) an emulsifier in an amount of 0.1% to 4% by weight; (d) an acid or base in an amount of 0.1% to 4% by weight; and (e) water in an amount of 25% to 60% by weight.

[0066] Because the compositions described herein can be prepared without the need for high activation temperatures, the compositions can be used in a variety of applications (e.g., warm mix asphalt applications performed at 120°C to 140°C) to provide sufficient crosslinking at a variety of temperatures. For example, the composition can be blended with an asphalt composition at a temperature of 160°C or less, 140°C or less, or 120°C or less. Depending on the extent of the network formed by the crosslinking reaction between the polymer and / or asphalt and the crosslinking agent, the compositions and methods disclosed herein can also provide greater control over, for example, polymer-modified asphalt. In addition, the compositions and methods disclosed herein do not require the use of sulfur, and therefore can reduce hydrogen sulfide (H2S) emissions. For example, in some embodiments, the asphalt composition is substantially free of sulfur or sulfur-based crosslinking agents. In other words, the asphalt composition can be prepared without the use of a sulfur-based crosslinking agent.

[0067] In some embodiments, the compositions disclosed herein can be used in paints, coatings, paper coatings or bonding compositions, carpet compositions (e.g., carpet backings), foams or adhesives. In some embodiments, one or more thickeners (rheology modifiers) can be added to increase the viscosity of the composition. Suitable thickeners may include, but are not limited to, acrylic copolymer dispersions, hydroxyethyl cellulose, guar gum, jaguar, carrageenan, xanthan gum, acetyl gum, konjac, mannan, xyloglucan, carbamates and mixtures thereof sold from BASF Corporation (Florham Park, New Jersey (Florham Park, NJ)) with STEROCOLL and LATEKOLL trademarks. Thickeners can be used as aqueous dispersions or emulsions, or as solid powders added to the composition formulation.

[0068] The compositions described herein may include, for example, additives such as dispersants, initiators, stabilizers, chain transfer agents, buffers, salts, preservatives, flame retardants, wetting agents, protective colloids, biocides, corrosion inhibitors, crosslinking promoters, and lubricants. Exemplary dispersants may include sodium polyacrylate in aqueous solution, such as those sold under the trademark DARVAN by RT Vanderbilt Co., Norwalk, CT.

[0069] Paint and coating compositions may, for example, include one or more pigments or dyes. Exemplary composition pigments include titanium dioxide composition pigments, MIRAGLOSS 91 (a kaolin composition pigment commercially available from BASF), LOPAQUE M (a kaolin composition pigment commercially available from Thiele Kaolin Company), and HYDROCARB 90 (a calcium carbonate composition pigment commercially available from Omya Paper). In some embodiments, the composition may include one or more dyes or colored pigments. Exemplary dyes may include basic dyes, acid dyes, anionic direct dyes, and cationic direct dyes. Exemplary colored pigments include organic pigments and inorganic pigments in the form of anionic pigment dispersions and cationic pigment dispersions.

[0070] By way of non-limiting illustration, examples of certain embodiments of the present disclosure are given below.

[0071] method

[0072] Also provided is a method for preparing the asphalt composition described herein. In some embodiments, the method may include preparing a latex composition of a polymer. The latex composition may be prepared by polymerizing monomers (such as styrene and butadiene monomers) in an aqueous emulsion polymerization reaction at a suitable temperature. The polymerization may be carried out at low temperatures (i.e., cold polymerization) or at high temperature methods (i.e., hot polymerization). In some embodiments, the polymerization may be carried out at low temperatures, such as 30°C or lower (e.g., 2°C to 30°C, 2°C to 25°C, 5°C to 30°C, or 5°C to 25°C). In some embodiments, the polymerization may be carried out at high temperatures, such as 40°C or higher, 50°C or higher, or 60°C or higher. In some embodiments, the high temperature may be 40°C to 100°C, 40°C to 95°C, or 50°C to 90°C.

[0073] The polymerized polymer can be prepared using a continuous, semi-batch (semi-continuous) or batch process. In some examples, a continuous process can be used to prepare a polymer by continuously feeding one or more monomer streams, a surfactant stream, and an initiator stream to one or more reactors. The surfactant stream comprises a surfactant and water, and in some embodiments can be mixed with an initiator stream.

[0074] Polymerization can be carried out in the presence of molecular weight regulators to reduce the molecular weight of the copolymer of other additives, such as dispersants, stabilizers, chain transfer agents, buffers, salts, preservatives, flame retardants, wetting agents, protective colloids, biocides, crosslinking accelerators, antioxidants, antiozonants, pre-vulcanization inhibitors and lubricants. In some embodiments, additives can be added to the latex composition after the polymerization. The latex composition can be agglomerated, and water is removed to produce the desired solid content, for example, using chemical agglomeration, frozen agglomeration or pressure agglomeration. In some embodiments, the solid content is 55% or greater, 60% or greater, or 65% or greater.

[0075] In some embodiments, the latex composition may have an overall anionic charge, a nonionic charge, or a cationic charge. One of ordinary skill in the art understands that the overall charge of the latex composition can be affected by the surfactant used, the specific monomers used to form the polymer in the latex composition, and the pH of the latex composition.

[0076] In some embodiments, the latex composition can be substantially free of coagulum or polymer residue when blended with a cationic surfactant or anionic surfactant used to prepare a cationic asphalt emulsion or anionic asphalt emulsion, respectively. The latex composition is substantially free of coagulum if it can be filtered through a 150 micron filter and leaves less than 0.2 wt.% residue based on the total weight of the latex composition.

[0077] The method of preparing an asphalt emulsion may include contacting asphalt with a latex composition as described herein. In some embodiments, the latex composition is cationic by incorporating a cationic reversal surfactant. In some embodiments, a cationic reversal surfactant is not added to the styrene-butadiene and styrene-butadiene-based latex compositions of the present invention. In some embodiments, an anionic reversal surfactant is not added to the styrene-butadiene latex composition of the present invention to impart a negative charge to the latex before being used in an anionic asphalt emulsion. The specific components in the soap tank (including asphalt, latex composition, and surfactant) can be mixed together by any means known in the art. The specific components can be mixed together in any order.

[0078] Specific components including asphalt, latex composition, and soap tank surfactant solution may be fed into a colloid mill at a temperature below 100°C (eg, 60°C to 95°C) where high shear mixing produces an asphalt emulsion having asphalt droplets dispersed in water.

[0079] The droplets in the asphalt emulsion may have a narrow particle size distribution. In some embodiments, the droplets in the asphalt emulsion may have a median particle size of 15 μm or less, 14 μm or less, 13 μm or less, 12 μm or less, 11 μm or less, 10 μm or less, 9 μm or less, 8 μm or less, 7 μm or less, 6 μm or less, or 5 μm or less and / or 5 μm or more, 6 μm or more, 7 μm or more, 8 μm or more, 9 μm or more, or 10 μm or more. In some embodiments, the droplets in the asphalt emulsion may have an average particle size of 15 μm or less, 14 μm or less, 13 μm or less, 12 μm or less, 11 μm or less, 10 μm or less, 9 μm or less, 8 μm or less, 7 μm or less, 6 μm or less, or 5 μm or less and / or 5 μm or more, 6 μm or more, 7 μm or more, 8 μm or more, 9 μm or more, or 10 μm or more. In some embodiments, the droplets in the asphalt emulsion may have a median particle size of 3 μm to 15 μm. In some embodiments, the droplets in the asphalt emulsion may have a median distribution of droplet particles with a standard deviation of less than 30%, less than 25%, less than 20%, less than 15%, or less than 10%.

[0080] In the absence of a thickener, when the asphalt is present in an amount of 65% by weight based on the asphalt emulsion, the asphalt emulsion may have a viscosity of 100 cp or more. In the case where the asphalt content is less than or greater than 65% by weight, the asphalt content may be adjusted by adding or removing water. In some embodiments, when the asphalt is present in an amount of 65% by weight based on the asphalt emulsion, the asphalt emulsion may have a viscosity of 150 cp or more, 200 cp or more, 250 cp or more, 300 cp or more, 350 cp or more, 400 cp or more, 450 cp or more, 500 cp or more, 600 cp or more, 700 cp or more, 800 cp or more, 900 cp or more, 1000 cp or more, 1500 cp or more, 2000 cp or more, or 2500 cp or more. In some embodiments, when the asphalt is present in an amount of 65 wt % based on the asphalt emulsion, the asphalt emulsion may have a viscosity of 2500 cp or less, 2000 cp or less, 1500 cp or less, 1250 cp or less, 1000 cp or less, 950 cp or less, 900 cp or less, 850 cp or less, 800 cp or less, 750 cp or less, 700 cp or less, 650 cp or less, 600 cp or less, 550 cp or less, 500 cp or less, 400 cp or less, 250 cp or more, 300 cp or less, or 200 cp or less. In some embodiments, when asphalt is present in an amount of 65 wt % based on the asphalt emulsion, the viscosity of the asphalt emulsion may be from 100 cp to 2500 cp, for example, from 100 cp to 1500 cp, from 100 cp to 1000 cp, from 100 cp to 800 cp, from 100 cp to 600 cp, from 100 cp to 500 cp, from 200 cp to 1500 cp, from 200 cp to 1000 cp, from 200 cp to 800 cp, from 200 cp to 600 cp, from 200 cp to 500 cp, from 100 cp to 500 cp, from 100 cp to 450 cp, or from 150 cp to 500 cp. In some embodiments, the addition of a phosphoric acid-reversed cationic latex composition and / or aluminum sulfate to an asphalt emulsion can result in an increase in viscosity of 1 times or greater, 2 times or greater, 3 times or greater, 4 times or greater, 5 times or greater, 6 times or greater, or up to 10 times or greater compared to an asphalt emulsion without the phosphoric acid-reversed cationic latex composition and / or aluminum sulfate.

[0081] In some embodiments, an asphalt emulsion using a PG 58-28 base asphalt may have a softening point of 65°C or higher (e.g., 70°C or higher, 75°C or higher, or 80°C or higher). In some embodiments, an asphalt emulsion using a PG 58-28 base asphalt may have a softening point of 85°C or lower (e.g., 80°C or lower, 75°C or lower, or 70°C or lower). In some embodiments, an asphalt emulsion using a PG 58-28 base asphalt may have a softening point of 65°C to 85°C or 70°C to 80°C. Ring and ball softening point tests, such as those described in ASTM D36 and / or AASHTO T53, can be used to measure the temperature at which an asphalt composition becomes soft and is able to flow.

[0082] The asphalt emulsions described herein may comply with the standards of ASTM D977, ASTM D2397, AASHTO M140, and AASHTO M208.

[0083] The latex composition can be used to prepare a polymer-modified hot mix asphalt composition. Hot mix asphalt can be prepared, for example, by blending asphalt, the latex composition described herein, and optionally an alkaline salt at a blending temperature exceeding the boiling point of water. In some embodiments, the pH of the latex composition can be 7 or less, as described herein. In some embodiments, the latex composition can be anionic. For example, the latex composition can include a carboxylated polymer. In some embodiments, the latex composition can be nonionic. In some embodiments, the latex composition can be cationic, for example, by including a cationic surfactant. The blending temperature of the hot mix asphalt can be 150°C or higher or 160°C or higher and 200°C or lower. When the asphalt is present in an amount of 95% by weight based on the hot mix asphalt composition, the hot mix asphalt composition is substantially free of water and can have, for example, a viscosity of 3000cp or less, 2500cp or less, 2000cp or less, or 1500cp or less at 135°C. In some embodiments, when the asphalt is present in an amount of 95% by weight based on the hot mix asphalt composition, the hot mix asphalt composition may have a viscosity of 1000 cp or greater, 1250 cp or greater, 1500 cp or greater, 2000 cp or greater, or 2500 cp or greater. In some embodiments, when the asphalt is present in an amount of 95% by weight based on the hot mix asphalt composition, the viscosity of the hot mix asphalt composition may be 1000 cp to 3000 cp, such as 1000 cp to 2500 cp, 1000 cp to 2000 cp, 1500 cp to 2500 cp, or 1500 cp to 2000 cp. When added to the hot mix asphalt, the latex composition may be in the amounts described above, but the resulting hot mix asphalt will contain less latex composition because the water is evaporated, leaving the latex polymer and any other non-volatile additives. For example, the latex polymer can be present in the hot mix asphalt composition in an amount of 0.05 wt.% to 10 wt.% (e.g., 0.5 wt.% to 3 wt.%) based on the weight of the hot mix asphalt composition. In some embodiments, the hot mix asphalt composition has a pH of 7 or less or 6 or less (e.g., 1.5 to 6), as described herein.

[0084] Methods of using the asphalt compositions described herein are disclosed. The asphalt compositions can be applied to a surface to be treated, restored, or sealed. Prior to applying the asphalt composition, the surface to be treated is typically cleaned to remove excess surface soil, weeds, and contaminants by, for example, brushing the surface, blasting the surface with compressed air, or washing the surface. The asphalt composition can be applied using any suitable method for applying a liquid to a porous surface, such as brushing, wiping, and drawing or spraying.

[0085] In some embodiments, once the asphalt composition is applied, the surface is wetted, thereby forming a layer over at least a portion of the surface and typically over at least a majority (e.g., greater than 50%). In some embodiments, when the asphalt emulsion is applied to the surface, water loss occurs in the emulsion, primarily due to adsorption of water. The water also delivers the asphalt and cationic latex composition to the surface. In some embodiments, the asphalt emulsion penetrates and adheres to the surface to which it is applied, solidifies in a relatively fast time, and provides a watertight and airtight barrier on the surface. The asphalt emulsion layer also promotes adhesion between older surfaces and later applied surface treatment layers. It is desirable that the asphalt composition be easy to apply and have a sufficient shelf life.

[0086] Aggregate can be blended into the asphalt composition and then applied to the surface. In some embodiments, the aggregate can be applied to the asphalt composition after the aggregate is applied to the surface. For example, sand can be applied to the asphalt composition after the sand is applied to the surface, for example if the composition will be used as an adhesion layer to reduce the tackiness of the surface. As will be appreciated by those skilled in the art, the asphalt composition and optionally the aggregate can be compacted after being applied to the surface.

[0087] The asphalt composition can be used for a road surface or a paved surface. A road surface or a paved surface is a hard surface capable of carrying pedestrians or vehicles, and may include surfaces such as highways / roads, parking lots, bridges / overpasses, runways, lanes, vehicle paths, running paths, walkways, etc. The asphalt composition can be applied directly to an existing paved surface, or it can be applied to an unpaved surface. In some embodiments, the asphalt composition can be applied to an existing paved layer as a bonding layer, and a new layer including asphalt (such as a hot mix layer) is applied to the bonding layer. The asphalt composition can be applied to a "cold" surface, i.e., a surface with a temperature below 40°C, or it can be applied to a high temperature (e.g., 50°C to 120°C, 55°C to 100°C, or 60°C to 80°C) surface.

[0088] In some embodiments, the asphalt composition can be used as an adhesion layer or coating. The adhesion layer is a very light spray application of a diluted asphalt emulsion that can be used to promote adhesion between an existing surface and a new asphalt application. The adhesion layer plays a role in providing a certain degree of adhesion or adhesion between asphalt layers, and in some cases, the layers can be melted together. The adhesion layer also plays a role in reducing the slippage and sliding of the layer relative to other layers in the pavement structure during use or due to the wear and tear of the pavement structure and weathering. In some embodiments, the asphalt composition can be applied to an existing paving layer (such as a hot mix layer) as an adhesion layer, and a new layer (such as a hot mix layer) comprising asphalt can be applied to the adhesion layer. As will be understood by those skilled in the art, the adhesion layer does not usually contain aggregate, but sand can be applied to the adhesion layer after application as described herein.

[0089] As described herein, the bituminous composition is fast-curing / drying. For example, when the bituminous composition is used as an adhesive coating, the coating is cured rapidly so that the pavement layer can be applied to the coating in a few hours to a few days after the emulsion is applied to the substrate. In some embodiments, the applied composition can be cured in 15 minutes to 45 minutes, and can be fast-cured in less than 1 minute to 15 minutes after the composition is applied to the exposed surface. The curing rate will depend on the application rate, the used dilution rate, the base condition, the weather and other similar considerations. If the prepared pavement surface or the base contain excessive moisture, the curing time of the bituminous composition may be increased.

[0090] In some embodiments, the asphalt composition may also be used as a fog seal. A fog seal is a surface treatment that applies a light application of the composition to an existing paved surface, such as a parking lot, to provide an enriched pavement surface that appears new and black. In some embodiments, the fog seal will contain fillers, such as carbon black, to darken the composition. As will be appreciated by those skilled in the art, the fog seal may not contain aggregate. Fog seal compositions, like bond coat compositions, have also been demonstrated as low-track or "trackless" coatings.

[0091] In some embodiments, the asphalt composition can be used as a chip seal composition. Chip seal is the most common surface treatment for low traffic roads. The chip seal composition can be applied to the surface and then the aggregate is applied. In some embodiments, the asphalt composition can be used for micro-surfacing applications. Micro-surfacing is designed to achieve rapid traffic restoration and has the ability to treat high traffic roads. For micro-surfacing compositions, the aggregate can be mixed with the cationic asphalt composition before being applied to the surface.

[0092] In some embodiments, the asphalt composition may be used in a paint, coating, paper coating or bonding composition, carpet composition (eg, carpet backing), foam, or adhesive.

[0093] Example

[0094] Preparation of non-carboxylated styrene-butadiene latex

[0095] Example 1. A non-carboxylated styrene-butadiene latex was prepared as follows. A copolymer derived from 41.5 parts by weight of styrene, 2.5 parts by weight of acrylamide, and 56 parts by weight of butadiene was prepared. Styrene feed, butadiene feed, initiator feed comprising an aqueous solution of sodium persulfate initiator (1.15 parts by weight of total monomers), and tert-dodecyl mercaptan (0.75 parts by weight of total monomers) were added over 6 hours to a preheated reactor (92° C.) containing water, polystyrene seed latex (0.63 parts by weight of total monomers), and TRILON BX (0.02 parts by weight of total monomers) (ethylenediaminetetraacetic acid commercially available from BASF Corporation, Florham Park, NJ). Stabilization of the latex particles during polymerization was achieved by feeding an aqueous solution of a 10 mole ethylene oxide adduct of a tridecanol surfactant (2.0 parts by weight of total monomers) during polymerization. In addition, 0.12 parts of tetrasodium pyrophosphate were fed to the reactor during polymerization. The temperature was maintained at 92°C throughout the polymerization process. After the polymerization process, the latex dispersion was stripped from residual monomer to provide an aqueous dispersion having a residual styrene content of less than 400 ppm.

[0096] The following examples were prepared according to the same general procedure as in Example 1.

[0097]

[0098] g = grams

[0099] Preparation of asphalt emulsion

[0100] A cationic styrene-butadiene latex composition is prepared by mixing a cationic surfactant solution (such as a fatty amine derivative having a pH of 1 to 3) with a styrene-butadiene latex. The styrene-butadiene latex does not contain a "reverse" cationic surfactant, i.e., a cationic surfactant that imparts a cationic charge to the latex before blending the latex with the cationic surfactant solution. Optionally, the styrene-butadiene latex contains a cationic surfactant and, before blending with the cationic surfactant solution, is "reversed" with hydrochloric acid to impart a cationic charge to the latex. The cationic surfactant solution containing the latex composition and molten asphalt is pumped into a colloid mill, where high shear mixing produces an asphalt emulsion having asphalt droplets dispersed in water. The amount of polymer is 3 wt % based on asphalt solids. Examples 5 to 8 are prepared and the viscosity and particle size of the asphalt emulsions are measured. The standard deviation is calculated.

[0101] Example 5 - Preparation of the Asphalt Emulsion of the Present Invention

[0102]

[0103] Example 6 - Preparation of the Asphalt Emulsion of the Invention

[0104]

[0105] Example 7 - Preparation of the Asphalt Emulsion of the Present Invention

[0106]

[0107] Example 8 - Comparative Asphalt Emulsion Preparation

[0108]

[0109] Asphalt PG 58-28 or Paving Asphalt PG 58-28 is a performance graded (PG) asphalt derived from a specially selected crude oil through a carefully controlled refining process. The first number in the PG designation specifies the maximum design temperature; the second number specifies the minimum design temperature. For example, PG 58-28 asphalt meets an average 7-day maximum pavement design temperature of 58°C and a minimum design temperature of -28°C.

[0110] Determination of particle size

[0111] The particle size distribution is determined by quasi-elastic light scattering (QELS), also known as dynamic light scattering (DLS), according to ISO 13321:1996 standard. The determination is carried out using a high-performance particle size classifier (Malvern) at 22°C and a wavelength of 633 nm. For this purpose, a sample of the aqueous polymer dispersion is diluted and the dilution is analyzed. In the case of DLS, the aqueous dilution may have a polymer concentration in the range of 0.001 wt.-% to 0.5 wt.-%, depending on the particle size. In most cases, a suitable concentration is 0.01 wt.-%. The particle size values ​​reported in Table 1 are the z-average values ​​of the cumulative evaluation of the measured values ​​of the measured autocorrelation function. Figure 1 In the specification, CRS-2LM refers to a modified cationic rapid setting latex, where 2 refers to the viscosity range.

[0112] Table 1. Particle size comparison between asphalt emulsions prepared from Examples 2, 3, and 4 and commercial cationic SBR Compare .

[0113]

[0114] Table 1 and Figure 1 It was shown that the emulsion droplet size of the latex polymer modified asphalt composition was much narrower compared to the commercial SBR latex modified asphalt emulsion.

[0115] Penetration testing of asphalt emulsions

[0116] The asphalt emulsion prepared according to the above method was subjected to penetration test according to ASTM D-5 protocol. The residue was recovered by evaporation according to ASTM 6934. The measurement of the penetration of a standard needle in the recovered asphalt binder sample was carried out under the following conditions:

[0117] Load = 100g

[0118] Temperature = 25°C

[0119] Time = 5 seconds

[0120] Depth of penetration is measured in dmm.Example 2 and Example 3, both of which contained no cationic inversion surfactant, were then blended with a cationic surfactant solution at low pH and co-milled with molten asphalt in a mill under shear to produce an asphalt emulsion.

[0121] Table 2. Permeability of asphalt emulsions containing Example 2 and Example 3 compared to commercial cationic SBR .

[0122]

[0123]

[0124] Table 2 shows the higher permeability of the asphalt emulsion modified with Example 3 (Example 6) compared to the residue of the emulsion modified with commercial cationic SBR latex. For the asphalt residue modified with Example 2 (Example 5), the permeability is lower than the emulsion modified with commercial cationic SBR latex. The penetration test is used as a measure of consistency, and a higher value indicates a softer consistency. It is surprisingly found that the addition of latex polymer Example 3 (Example 6) results in a softer consistency of the asphalt emulsion compared to the asphalt emulsion modified with commercial cationic SBR latex. Softer consistency is advantageous due to ductility and temperature sensitivity.

[0125] Scanning test of asphalt emulsion

[0126] The emulsions prepared according to the above method were evaluated using ASTM D-7000, Standard Test Method for Sweep Test of Bituminous Emulsion Surface Treatment Samples, which measures the curing performance characteristics of asphalt emulsions and aggregates by sweeping to simulate surface treatment in the laboratory.

[0127] Table 3. Comparison of scanning test asphalt emulsions and commercial cationic SBR .

[0128]

[0129] Table 3 shows that the asphalt emulsions modified with non-carboxylated styrene-butadiene latex Examples 2 and 3 without inverting surfactant and non-carboxylated styrene-butadiene-methyl methacrylate latex Example 4 have better scanning performance than the asphalt emulsion modified with commercial cationic SBR latex.

[0130] The scope of the compositions and methods of the appended claims is not limited by the specific compositions and methods described herein, which are intended to illustrate several aspects of the claims, and any compositions and methods that are functionally equivalent are intended to fall within the scope of the claims. In addition to the compositions and methods shown and described herein, various modifications to the methods are intended to fall within the scope of the appended claims. Further, although only certain representative compositions and method steps disclosed herein are specifically described, other combinations of these compositions and method steps are also intended to fall within the scope of the appended claims, even if not specifically described. Therefore, combinations of steps, elements, components or ingredients may be explicitly or less explicitly mentioned herein, however, other combinations of steps, elements, components and ingredients are included, even if not explicitly stated. As used herein, the term "including" and its variants are used synonymously with the term "comprising" and its variants, and are open, non-limiting terms. Although the terms "including" and "comprising" have been used herein to describe various embodiments, the terms "consisting essentially of" and "consisting of" may be used to replace "including" and "comprising" to provide more specific embodiments of the present invention, and are also disclosed. Except in the examples or where otherwise indicated, all numbers expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims should at least be understood, and not as an attempt to limit the application of the doctrine of equivalents to the scope of the claims, to be construed in light of the number of significant digits and ordinary rounding techniques.

Claims

1. An asphalt emulsion composition, comprising: (i) bitumen, (ii) non-carboxylated latex, (iii) less than 10 wt. % of an inverting surfactant, based on the total weight of the composition, and (iv) optionally water.

2. The composition of claim 1, wherein the non-carboxylated latex comprises a styrene-butadiene copolymer.

3. The composition of claim 1, wherein the non-carboxylated latex comprises a styrene-butadiene-acrylate terpolymer.

4. The composition of claim 1, wherein the non-carboxylated latex copolymer comprises styrene-butadiene-acrylonitrile copolymer.

5. The composition of claim 1, wherein the non-carboxylated latex comprises styrene-butadiene-acrylamide copolymer.

6. The composition of claim 1, wherein the non-carboxylated latex copolymer comprises styrene-butadiene-acrylate-acrylonitrile copolymer.

7. The composition of claim 1, wherein the non-carboxylated latex comprises styrene butadiene latex which is a blend of a styrene-butadiene latex polymerized at a high polymerization temperature and a styrene-butadiene latex polymerized at a low polymerization temperature.

8. The composition according to claim 7, wherein the high polymerization temperature is 40 to 100°C, and the low polymerization temperature is -5 to 40°C.

9. The asphalt composition of claim 1, wherein the non-carboxylated latex is free of invert surfactant.

10. The asphalt composition of claim 1, wherein the non-carboxylated latex is free of a cationic inverting surfactant.

11. The asphalt composition of claim 1, wherein the non-carboxylated latex does not produce coagulum when blended with a cationic surfactant in the preparation of a polymer-modified cationic asphalt emulsion.

12. The asphalt composition of claim 1, wherein the non-carboxylated latex does not produce coagulum when blended with an anionic surfactant in the preparation of a polymer-modified anionic asphalt emulsion.

13. The composition of any one of claims 1 to 12, wherein the ratio of styrene to butadiene is in the range of 80 / 20 to 20 / 80 on a weight basis.

14. The composition of any one of claims 1 to 13, wherein the ratio of styrene to butadiene is 25 / 75 on a weight basis.

15. The composition of any one of claims 1 to 14, wherein the ratio of styrene to butadiene is 50 / 50 on a weight basis.

16. The composition of any one of claims 1 to 15, wherein latex solids range from 30 wt.% to 75 wt.%, based on the total weight of the composition.

17. A method of forming the composition of claim 1, the method comprising contacting a non-carboxylated latex, asphalt, and a cationic surfactant solution to form an asphalt emulsion.

18. The method of claim 17, wherein the non-carboxylated latex, asphalt and cationic surfactant solution are co-milled in a colloid high shear mill to form a cationic asphalt emulsion.

19. The method of claim 17, wherein the non-carboxylated latex is post-added to the cationic asphalt emulsion.

20. A method of forming the composition of claim 1, the method comprising contacting a non-carboxylated latex, asphalt, and an anionic surfactant solution to form an asphalt emulsion.

21. The method of claim 20, wherein the non-carboxylated latex, asphalt and anionic surfactant solution are co-milled in a colloid high shear mill to form an anionic asphalt emulsion.

22. The method of claim 30, wherein the non-carboxylated latex is post-added to an anionic asphalt emulsion.

23. A method of forming the composition of claim 1, the method comprising contacting a non-carboxylated latex, asphalt, and a nonionic surfactant solution to form an asphalt emulsion.

24. The method of claim 23, wherein the non-carboxylated latex, asphalt and non-ionic surfactant solution are co-milled in a colloid high shear mill to form a non-ionic asphalt emulsion.

25. The method of claim 23, wherein the non-carboxylated latex is post-added to a non-ionic asphalt emulsion.

26. An adhesion layer comprising the bituminous composition according to any one of claims 1 to 16.

27. A mist seal comprising the asphalt composition according to any one of claims 1 to 16.

28. A chip seal comprising the asphalt composition according to any one of claims 1 to 16.

29. A paving asphalt comprising the asphalt composition according to any one of claims 1 to 16.

30. The bitumen emulsion composition of claims 1 to 13 for use in waterproofing, roofing, paints, coatings, paper binders or coatings, foams, adhesives, powders and carpet applications.

31. A styrene-butadiene latex prepared by emulsion polymerization, wherein the latex is cold polymerized.

32. A styrene-butadiene latex prepared by emulsion polymerization, wherein the latex is thermally polymerized.

33. A hot mix asphalt composition comprising the styrene-butadiene copolymer latex according to any one of claims 31 to 32.

34. The hot mix asphalt emulsion composition of claim 33, wherein the particle size of the styrene-butadiene copolymer latex is less than 200 nm.

35. An asphalt emulsion composition comprising the styrene-butadiene copolymer latex according to any one of claims 31 to 32.

36. The asphalt emulsion composition of claim 35, wherein the particle size of the styrene-butadiene copolymer latex is less than 200 nm.

Citation Information

Patent Citations

  • Accelerators for cationic aqueous bituminous emulsion-aggregate slurries

    US5096495A

  • Cationic aqueous bituminous emulsion-aggregate slurries

    US5160453A

  • Cationic aqueous bituminous emulsion-aggregate slurries

    US5443632A